(untitled) (International Journal of Engineering and Computer Science, 2023)
In automotive and other manufacturing industries making light weight part with corrosion resistance was the challenges. Looking at these challenges, casting part is the best replacement which can fulfil both the requirements corrosion resistance and light weight. Minimizing the operational cost is the today’s requirement .High pressure die casting process is the best solution, multicavity die can be used to produce the components with in few seconds. In HDPC there is inherent characteristics of porosity or voids or shrinkage porosity these casting defects can be managed and controlled but it cannot be eliminated permanently. Looking at this phenomenon, in this research work process parameters optimization have been taken to reduce porosity /shrinkage porosity those parameters are holding furnace temperature ,die temperature , first phase plunger speed, second phase plunger speed and third phase intensification pressure or accumulated pressure best result achieved on following parameters. Holding Furnace temperature 700 ˚C, Die temperature 195 ˚ ˚C First phase speed 0.23 m/s, second phase speed 2.5 m/s, intensification pressure 285 bar. Taguchi methodology have been used for optimization of process parameters. UTM has been used for testing strength, radiography machine used for porosity level assessment and spectro machine have been used for chemical composition.